The application of a multidisciplinary methodological approach to the training of physical therapists in the process of rehabilitation of a patient with a gunshot wound to the spinal cord - Yakovenko , Olga; Ovdii , Mariia; Volianskyi , Oleksii; Kikh, Andrii; Krasiuk , Sergii (The Ukrainian Scientific Medical Youth Journal, 2023)
rehabilitation is one of the key areas of medicine, especially during periods of full-scale war, when militaries and civilians require long-term rehabilitation interventions. The use of a multidisciplinary approach in rehabilitation made it possible to expand the scope and opportunities of rehabilitation treatment and improve the recovery of patients. A physical therapist plays an important role in a multidisciplinary team and carries out rehabilitation measures to eliminate, stop or reduce pain, restore body functions, achieve a normal level of health, physical independence and activity, optimal physical condition and well-being. The training of qualified physical therapists is an important component of successful rehabilitation. The article presents the results of the cooperated work of specialists of the multidisciplinary team of the Military Medical Clinical Treatment and Rehabilitation Center of city Irpin, and physical therapy higher education applicants of the Department of Physical Rehabilitation and Sports Medicine of the Bogomolets National Medical University. The aim of the work was to improve the practical skills of physical therapy higher education applicants by integrating them into the work process of a multidisciplinary rehabilitation team for the rehabilitation of a patient with a gunshot wound to the spinal cord. Higher education applicants took part in the rehabilitation examination and had the opportunity to expand practical skills in this direction. The team of specialists conducted the following rehabilitation tests and obtained results - according to the ASIA scale, the degree of damage to the patient’s spinal cord is complete - there is no sensitivity and motor function of the S4-S5 segments, according to the modified Rankin scale 5 points, which corresponds to severe functional disability; according to the Barthel index, 10 points, which corresponds to the patient’s complete dependence on external assistance, according to manual muscle testing, the strength of the muscles of the upper shoulder girdle corresponded to 3 points - the full amplitude of movement against the force of gravity. On the basis of the obtained results, the multidisciplinary team determined the main violations according to the domains of the international classification of functioning, and in accordance with them, the higher education applicants developed the key goals of rehabilitation and methods that must be included in the rehabilitation process. Physical therapy higher education applicants conducted rehabilitation interventions aimed at improving patient mobility and self-care, prevention of bedsores, contractures, improvement of the musculoskeletal system, and increased tolerance to physical exertion. After six weeks of the rehabilitation process, repeated rehabilitation examinations were carried out, positive dynamics were admitted according to the Rankin scale, according to the Barthel index and manual muscle testing. The higher education applicants survey showed that while working in a multidisciplinary team, physical therapist higher education applicants managed to expand their knowledge, practical skills and acquire the necessary components for work and close interaction with all team members, to increase the effectiveness of rehabilitation measures for a patient with a spinal cord injury.